Food safety management programs applications, best practices, and compliance - Newslow, Debby L.
The value of an effective well-defined, implemented, and maintained management system is priceless. Based on the requirements of ISO 900 I, ISO 22000, and PAS 220, this text provides a collection of participation-based tools that can be applied to the development, implementation, and maintenance of a management-based system in the food industry. The book clearly explains how to choose the right system for an organization, what the requirements are, how to identify gaps in the system, and ways to integrate these resources into individual operations. The author also compares ISO and HACCP programs as well as includes case studies from professionals